Sofosbuvir plus ribavirin for the treatment of patients with chronic genotype 1 or 6 hepatitis C virus infection in Hong Kong. Issue 1 (26th October 2015) - Lai, C. L.; Wong, V. W.‐S.; Yuen, M. F.; Yang, J. C.; Knox, S. J.; Mo, H.; Han, L. L.; Brainard, D. M.; Chan, H. L. Y.
Summary: Background: In Hong Kong, most patients with hepatitis C virus (HCV) have either genotype 6a or 1b infection. Aim: To evaluate the efficacy and safety of sofosbuvir with ribavirin in treatment‐naïve patients in Hong Kong with HCV genotype 1 or 6. Methods: In an open‐label study, patients were randomised to sofosbuvir 400 mg once daily plus ribavirin 1000–1200 divided twice daily for 12 ( n = 10), 16 ( n = 11) or 24 ( n = 10) weeks. The primary endpoint was the percentage of patients with HCV RNA < LLOQ (lower limit of quantification, 25 IU/mL) 12 weeks after cessation of therapy (SVR12). Results: All 31 patients (20 HCV genotype 1 and 11 genotype 6) had HCV RNA < LLOQ by Week 4 of treatment and at their last on‐treatment visit. SVR12 rates were high in all treatment groups: 100% (10/10) for 12 weeks, 100% (11/11) for 16 weeks and 90% (9/10) for 24 weeks of therapy. The only patient who did not reach SVR12 had genotype 1 HCV and relapsed at post‐treatment Week 4. Sofosbuvir with ribavirin was generally well tolerated. The most common adverse events were malaise (13%) and upper respiratory tract infection (13%), followed by anaemia (10%). No patients experienced serious adverse events. One patient discontinued treatment at Week 16 because of an adverse event. The event, upper respiratory tract infection, was not considered treatment related by the investigator. This subject achieved SVR12. Conclusions: The all‐oral regimen sofosbuvir plus ribavirin is effective in treatment‐naïve patients in Hong Kong with genotype 1 or 6 HCV. Trial registration number: NCT02021643.